2004
DOI: 10.1177/154405910408300309
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Colonization with Tannerella forsythensis and Loss of Attachment in Adolescents

Abstract: Colonization with Tannerella forsythensis may characterize the conversion of periodontally healthy sites into diseased sites. This three-year study describes the prevalence of T. forsythensis and its relationship to clinical loss of attachment (LOA) in a group of adolescents considered at risk of developing early chronic periodontitis. Adolescents with (LOA+) and without (LOA-) loss of attachment were examined at baseline and 1.5 and 3 yrs subsequently. On each occasion, attachment loss was measured on selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
2
25
0
5
Order By: Relevance
“…Furthermore, T. forsythia, but not P. gingivalis, was associated with, and predictive of, progressing attachment loss in older individuals with minimal periodontitis (Tran et al, 2001), by the PCR assay used in the current study. T. forsythia was detected more frequently from adolescents with progressing attachment loss than from non-progressing individuals (Hamlet et al, 2004). The current study also detected T. forsythia in health, consistent with its detection in periodontally healthy children, adolescents (Sirinian et al, 2002), and adults (Gmür et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, T. forsythia, but not P. gingivalis, was associated with, and predictive of, progressing attachment loss in older individuals with minimal periodontitis (Tran et al, 2001), by the PCR assay used in the current study. T. forsythia was detected more frequently from adolescents with progressing attachment loss than from non-progressing individuals (Hamlet et al, 2004). The current study also detected T. forsythia in health, consistent with its detection in periodontally healthy children, adolescents (Sirinian et al, 2002), and adults (Gmür et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies showed that the incidence of T. forsythia in the periodontal sulcus positively correlates with the clinical signs of periodontal disease and can be regarded as a risk indicator for attachment and bone loss (15,16,17). According to the work of Tanner et al (31), the incidence of P. gingivalis and T. forsythia in subgingival and tongue samples is associated with early periodontitis compared to the samples isolated from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…forsythensis has been shown to be one of three species associated with sites that have converted from periodontal health to disease (31). Indeed, the odds of loss of attachment in adolescents were shown to be 8.16 times greater in subjects colonized by T. forsythensis in a 3-year longitudinal study (11). In adults with a low prevalence and a low severity of periodontitis, subjects persistently colonized with T. forsythensis had 5.3 times higher odds of losing attachment at at least one site compared to the odds for those in whom the organism was not detected or only occasionally detected (33).…”
mentioning
confidence: 99%